Would order-by-order auctions be competitive? - ERNST, Thomas (Institutional Knowledge at Singapore Management University, 2023)
We model two different methods of executing segregated retail orders: broker's routing, whereby brokers allocate orders using market maker's overall performance, and order-by-order auctions, where market makers bid on individual orders, a recent SEC proposal. Order-by-order auctions improve market maker allocative efficiency, but face a winner's curse reducing retail investor welfare, particularly when liquidity is limited. Additional market participants competing for retail orders fail to improve total efficiency and investor welfare when entrants possess information superior to incumbent wholesalers. Existing Retail Liquidity Programs empirically suggest order-by-order auctions would attract few bidders in less liquid stocks and low-liquidity periods.